Management of motor neurone disease. Issue 926 (1st December 2002) - Howard, R S; Orrell, R W
Abstract : Motor neurone disease is a progressive neurodegenerative disorder leading to severe disability and death. It is clinically characterised by mixed upper and lower motor neurone involvement affecting bulbar, limb, and respiratory musculature. Recent guidelines have established diagnostic criteria and defined management of the condition. In a proportion of familial amyotrophic lateral sclerosis there is a mutation in the gene encoding the enzyme copper/zinc superoxide dismutase 1; this has allowed mutation screening and generated considerable laboratory based research. The diagnosis must be given with care and consideration and close follow up is essential. Management involves a multidisciplinary team based in the hospital and the community. Riluzole is the only drug shown to have a disease modifying effect and has been approved by the National Institute for Clinical Excellence. The essence of care is good symptomatic management, including nutritional support with percutaneous endoscopic gastrostomy and ventilatory care with non-invasive ventilation. Palliative care should be introduced before the terminal stages after careful discussion with the patient and carers. Knowledge of this condition has grown dramatically recently with a parallel improvement in treatment and ability to deal with the most troublesome problems.